Dietary protein intake and transition between frailty states in octogenarians living in New Zealand - Teh, Ruth (2021)
Funding Information: Funding: This research was funded by Health Research Council of New Zealand (HRC 09/068B; UoA ref: 3624940) and Ministry of Health New Zealand (MOH ref: 345426/00; UoA ref: 3703221) which funded the project management and data collection work; Nga¯ Pae o te Ma¯ramatanga (UoA ref: 3624946) which funded the Ma¯ori engagement and project management. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.